Mitochondrial intoxication - Roberto de Oliveira, Marcos (Academic Press, 2023)
Mitochondrial Intoxication explores the effects toxic molecules can have upon mitochondrial physiology in the human body. Each chapter is dedicated to a specific toxicant, including pollutants, food additives, illicit and pharmaceutical drugs, and heavy metals. This book considers the implications and impact these have upon mitochondria and the diseases that can result from dysfunction and impairment in the human body. Furthermore, the book provides an overview of mitochondrial physiology and assesses the advances and challenges in testing mitochondrial toxicity. Case studies exploring mitochondrial intoxication in pregnancy and in the geriatric population are also included.